2020
DOI: 10.29271/jcpsp.2020.08.833
|View full text |Cite
|
Sign up to set email alerts
|

Night Eating Syndrome According to Obesity Groups and the Related Factors

Abstract: Objective: To find the frequency of night eating syndrome (NES) in different obesity groups and to determine related factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 1 publication
(3 reference statements)
1
22
0
1
Order By: Relevance
“…The remaining 22 studies ( * Cleator et al, 2013 , 2014 ; * Dalle Grave et al, 2013 ; * Roer et al, 2014 ; * Baldofski et al, 2015 ; * McCune and Lundgren, 2015 ; * Royal et al, 2015 ; * Vander Wal et al, 2015 ; * Vinai et al, 2015a , b ; * Dorflinger et al, 2017 ; * Ferreira Pinto et al, 2017 ; * Nasirzadeh et al, 2018 ; * Zengin-Eroglu et al, 2018 ; * Loddo et al, 2019 ; * Tu et al, 2019 ; * Zickgraf et al, 2019 ; * Kara et al, 2020 ; * Latzer et al, 2020a , b ; * Uncu et al, 2020 ; * Ivezaj et al, 2021 ) were included in the systematic review for extraction of data (see Figure 1 for the overview of the study selection).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining 22 studies ( * Cleator et al, 2013 , 2014 ; * Dalle Grave et al, 2013 ; * Roer et al, 2014 ; * Baldofski et al, 2015 ; * McCune and Lundgren, 2015 ; * Royal et al, 2015 ; * Vander Wal et al, 2015 ; * Vinai et al, 2015a , b ; * Dorflinger et al, 2017 ; * Ferreira Pinto et al, 2017 ; * Nasirzadeh et al, 2018 ; * Zengin-Eroglu et al, 2018 ; * Loddo et al, 2019 ; * Tu et al, 2019 ; * Zickgraf et al, 2019 ; * Kara et al, 2020 ; * Latzer et al, 2020a , b ; * Uncu et al, 2020 ; * Ivezaj et al, 2021 ) were included in the systematic review for extraction of data (see Figure 1 for the overview of the study selection).…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 summarizes the three studies that outline the similarities and differences found in NES and BED patients based on demographic and psychological outcomes. For all 22 studies, a total of 4,502 participants were recruited across various clinical populations, i.e., ED patients (including NES) ( n = 947 across eight studies; * McCune and Lundgren, 2015 ; * Vander Wal et al, 2015 ; * Vinai et al, 2015a , b ; * Loddo et al, 2019 ; * Tu et al, 2019 ; * Latzer et al, 2020a , b ), patients with obesity ( n = 1,616 participants across seven studies; * Cleator et al, 2013 , 2014 ; * Dalle Grave et al, 2013 ; * Roer et al, 2014 ; * Dorflinger et al, 2017 ; * Kara et al, 2020 ; * Uncu et al, 2020 ), and those who have had bariatric surgery or are planning to undergo one (i.e., prebariatric surgery patients) ( n = 1,939 participants across seven studies; * Baldofski et al, 2015 ; * Royal et al, 2015 ; * Ferreira Pinto et al, 2017 ; * Nasirzadeh et al, 2018 ; * Zengin-Eroglu et al, 2018 ; * Zickgraf et al, 2019 ; * Ivezaj et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations